Study of KH Ahmad Dahlan Thoughts in Modernizing Islamic Education in Indonesia - Khaerudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is motivated by the thought of KH Ahmad Dahlan in reconstructing Islamic education that combines traditional education with western education. The mindset of the people at that time considered that the secular education system could not be elaborated with traditional education because it would damage the aqidah. This research aims to examine the phenomenon of KH. Ahmad Dahlan's life both in terms of sociohistorical so as to understand KH. Ahmad Dahlan's thoughts in modernizing Islamic education in Indonesia. This research uses a qualitative method with a descriptive approach. The type of research is a literature study, data sources in the form of literature sources both books, journal articles or previous research relevant to this research. This research technique is documentation. In the findings of the research, it was found that KH. Ahmad Dahlan is a Muslim intellectual figure and ulama who is known by all Indonesian people. The idea of KH. Ahmad Dahlan's thought was able to provide significant changes in the field of education. KH. Ahmad Dahlan designed in such way that the concept of Islamic education collaborated the traditional education system with the western education system, so that the modern education system was born until now.